Development and validation of a biotic ligand model for predicting chronic toxicity of lead to Ceriodaphnia dubia. (20th December 2013) - Nys, Charlotte; Janssen, Colin R.; Mager, Edward M.; Esbaugh, Andrew J.; Brix, Kevin V.; Grosell, Martin; Stubblefield, William A.; Holtze, Keith; De Schamphelaere, Karel A.C.
Abstract While it is increasingly being recognized that biotic ligand models (BLMs) are valuable in the risk assessment of metals in aquatic systems, the development of chronic BLMs has been less advanced for lead than for other metals. The authors investigated the univariate effects of Ca and pH on the chronic reproductive toxicity of Pb to Ceriodaphnia dubia at 4 levels. Calcium influenced chronic Pb toxicity to C. dubia only to a relatively small extent, whereas a high pH (8.2) provided strong protection against Pb toxicity (compared with lower pH levels). Based on this data set, a chronic Pb BLM for C. dubia was developed. The effect of pH was modeled as a single biotic ligand site competition by H+ with a log stability constant for binding of H+ to the biotic ligand (KHBL) of 7.6, while no other competitive constants were needed. The developed BLM was shown, in an independent validation with 3 other data sets, to be capable of predicting chronic Pb toxicity to different clones of C. dubia by an error of less than a factor of 2 in most synthetic and natural waters considered. The results add to the growing evidence that BLM–based risk assessment or water‐quality criteria for Pb are likely to be more appropriate relative to hardness‐based assessments or criteria. Environ Toxicol Chem 2014;33:394–403. © 2013 SETAC